PENGEMBANGAN GAME EDUKASI SUPER ALIEN GEC DI SMK NEGERI 1 SINTUK TOBOH GADANG - Dita Zuliany; Adlia Alfiriani; Ade Pratama (PeTeKa (Jurnal Penelitian Tindakan Kelas dan Pengembangan Pembelajaran), 2023)
Educational games are the most common type of educational media used to provide knowledge and improve user understanding through distinctive and interesting media. The learning media used is still based on textbooks and teaching materials, making it difficult for students to implement the material in the real world. The use of conventional learning media can reduce the attractiveness of students in paying attention to learning even though the facilities and infrastructure at this school are adequate. Such as the existence of computer labor, laptops, wi-fi networks and others. This type of research uses the R&D Research method refers to the research methodology used to produce target products and assess their effectiveness. In this study, the ADDIE (Analysis-Development-Implementation-Evaluate) research model will be used. This research produces educational games for use in the computer science curriculum of class X TJKT at SMK Negeri 1 Sintuk Toboh Gadang. Based on the results of the game validation threshold data analysis, which was approved by the validator with an accuracy rate of 84.29% with the category "Very Valid". Data analysis shows that the percentage of students who get a minimum score of 92.36% with the category "Very Practical" in educational games developed by computer science lecturers. And educational games made by students get a percentage of 88.19% with the category "Very Practical".